2022
DOI: 10.52633/jms.v4i2.201
|View full text |Cite
|
Sign up to set email alerts
|

Neuromarketing - Seeing the Unseen: Effect of In-Store Category Artwork, Structures and Packaging on Shopper’s Buying Behaviors in Pakistan

Abstract: Neuromarketing in the simplest terms is the intersection of brain research and marketing. Neuromarketing combines cognition, technology, and marketing. Neuromarketing is a relatively young branch of marketing that examines how consumers react to marketing stimuli. The term "neuromarketing" refers to the use of neuroscience in the marketing process. The neuromarketing impact of packaging and labeling on consumer buying behavior was examined in this paper; as packaging is a critical way of transmitting product i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
(33 reference statements)
0
1
0
Order By: Relevance
“…According to [19]; [20], corporate social responsibility, social media, advertising such as flyers and banners, and sales promotion have a relationship between consumer buying behavior on the product. 2.…”
Section: Consumer Demand For Kele-kele Honey Is Increasingmentioning
confidence: 99%
“…According to [19]; [20], corporate social responsibility, social media, advertising such as flyers and banners, and sales promotion have a relationship between consumer buying behavior on the product. 2.…”
Section: Consumer Demand For Kele-kele Honey Is Increasingmentioning
confidence: 99%
“…[4] reported that digital marketing has a positive influence and significantly increases sales results. Research conducted by [5], [6] found that the use of social media, especially Instagram in marketing coffee drink products, was very effective in disseminating promotions more quickly and costeffectively to customers compared to traditional media methods.…”
Section: Introductionmentioning
confidence: 99%